Transformation of Markets and Policy Instruments for Open Market Operations - Axilrod, S. (Washington, D.C. : International Monetary Fund, 1995)
As developing countries and economies in transition have relied on deregulated, competitive markets to spur growth, their central banks have shifted toward using open market operations as a tool of monetary policy. To be most effective, such operations require supportive changes in other policy instruments (reserve requirements, discount window), a competitive banking system and securities market, and adaptation of particular open market or market-type instruments used to the stage of, and potential for, market development. The paper assesses options available to a central bank for encouraging a competitive market architecture and designing instruments for implementation of open market operations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet